We move together: a realist evaluation of the Safe Motherhood Action Groups in Eastern Province, Zambia - Brynne Gilmore; Sara Dada; Aoife De Brún; Bellington Vwalika; Nachela Chelwa; Natasha Okpara; Mirriam Zulu (BMJ Global Health)
Introduction In Zambia, where less than half of pregnant women complete the continuum of care for maternal health, community engagement initiatives like the Safe Motherhood Action Groups (SMAGs) are used to mobilise communities and support maternal and newborn health (MNH) care-seeking. However, there is a lack of documented evidence on communication in community engagement and its implementation across diverse settings. This study examines how communication in community engagement influences MNH care-seeking in Zambia’s Eastern Province.Methods This realist evaluation used two iterative multi-method case studies to evaluate the SMAG programmes at Chibolya Urban Health Clinic and Jerusalem Rural Health Clinic. Data were collected from facility metrics, in-depth interviews, realist photovoice discussions, focus-group discussions and observations. Participants, including SMAGs (n=10), local leaders (n=2), pregnant women (n=10), community members (n=20), healthcare providers (n=4) and Ministry of Health stakeholders (n=4) were purposively sampled.Results Seven programme theories, informed by 50 context-mechanism-outcome configurations, were refined and organised to explain how the SMAG programme in Zambia works when communities are actively involved, messaging is relevant and relatable, SMAGs are trusted, SMAGs are familiar, the programme and facility are well-coordinated, the community perceives benefits from the messaging and SMAGs are motivated.Conclusion This realist evaluation offers research, practice and policy recommendations to enhance communication in community engagement for MNH, with potential applicability to other health domains. It emphasises trust and strong community-programme relationships as key drivers of effective and sustainable community engagement.